A Masterly Treatment of EU Law and Translation in a Single Book. Review of Colin D. Robertson’s Multilingual Law. A Framework for Analysis and Understanding. London and New York: Routledge, 2016, pp. 273. - BEDNAROVA-GIBOVA, Klaudia (Comparative Legilinguistics, 2017)
.